A Persistently Increasing Precipitation Trend Through the Holocene in Northwest China Recorded by Black Carbon δ13C From Sayram Lake - Jiang, Qingfeng; Zheng, Jianan; Yang, Yufeng; Zhao, Wenwei; Ning, Dongliang (Frontiers in Earth Science, 2020)
Precipitation is an important requirement for the stable and sustainable development of ecosystems and communities in arid areas, which are vulnerable to the influences of climate change. The changes in precipitation throughout the Holocene, as well as its long-term characteristics in arid northwest China, are not well understood, and records to reconstruct the precipitation trends are needed. Therefore, this study established a well-dated black carbon (BC) stable isotope-inferred (δ13C) precipitation record based on a sediment core from Sayram Lake, Tianshan Mountains (Xinjiang province, northwest China). The record spans the last 12880 cal. yr BP. Variations in BC δ13C showed that between ∼12280 and 9260 cal. yr BP, regional precipitation gradually decreased, but then increased continually until the present, with millennial to centennial scale fluctuations. During the Holocene, a distinct period of low precipitation was observed between 9800 and 8800 cal. yr BP, and two episodes of high precipitation were observed between 8000 and 7600, and 5800 and 2500 cal. yr BP. The maximum precipitation occurred at ∼3800 cal. yr BP. Generally, the persistently increasing precipitation trend is consistent with other records from arid northwest China and adjacent areas. The trend was possibly controlled by Northern Hemisphere solar insolation and associated substantial ice sheet remnants, due to the influence of the North Atlantic Ocean sea surface temperatures and intensities of the Westerlies, which regulate the transport of water vapor to Xinjiang. The results provide a better understanding of the mechanisms driving the evolution of precipitation through the Holocene.